2017
DOI: 10.1515/amtm-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water on Tribological Properties of Wood-Polymer Composites

Abstract: A B S T R A C TUtilization of ecological materials for appliances and products is one of the ways to achieve the goal of sustainability. Wood-polymer composites as a cheap, lightweight, durable and esthetic material has gained attention of scientists, engineers and consumers alike. Different kinds of polymeric matrices, plants used as the fillers, chemical of physical modifiers and processing technologies have already been widely studied. Nonetheless, surprisingly few information on WoodPolymer Composites' tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The effect of water asorption on hybrid composite fibers in accordance with ASTM D570 with specimen size 12X12X40 mm 3 . Water absorption tests were conducted by measuring the composite specimen in distilled water in beaker at room temperatiure for different tme durations as shown in Fig.…”
Section: Water Absorption Testmentioning
confidence: 97%
See 2 more Smart Citations
“…The effect of water asorption on hybrid composite fibers in accordance with ASTM D570 with specimen size 12X12X40 mm 3 . Water absorption tests were conducted by measuring the composite specimen in distilled water in beaker at room temperatiure for different tme durations as shown in Fig.…”
Section: Water Absorption Testmentioning
confidence: 97%
“…The mould box is prepared of mild steel with dimension of volume 300 X 300 X 25 mm 3 as shown in Fig. 1.…”
Section: Mould Boxmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in another study, three different liquid solutions were impregnated into wood, and their wear properties were examined (Hamdan et al 2010). Even fewer publications have been dedicated to the study of tribological properties of thermoplastic polymers and their composites incorporating natural fillers, including materials such as polyoxymethylene (Li et al 2008;Xiang et al 2012), polyethylene (Brostow et al 2016;Yang et al 2019;Al-Maqdasi et al 2022), polyvinyl chloride (Jiang et al 2017;, polypropylene (Aurrekoetxea et al 2008;Bajpai et al 2012;Mysiukiewicz and Sterzyński 2017;Ibrahim et al 2019;Mazzanti et al 2021), and polylactic acid (Mysiukiewicz and Sterzyński 2017). Despite the limited number of studies on the subject, a previous investigation indicated that the addition of wood flour reduced the CoF compared to the neat polymer (Aurrekoetxea et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Research works associated with the wood polymer composites (WPCs) can be divided into two main trends -decreasing materials' costs and enhancement of their properties (Mysiukiewicz and Sterzyński, 2017). The first trend is realized by searching for new lignocellulosic fillers from different kinds of agriculture wastes or by applying recycled polymers as matrices (Lewandowski et al, 2016).…”
Section: Introductionmentioning
confidence: 99%